The deserts of Bohemia : Czech fiction and its social context - Steiner, Peter (Cornell University Press, 2000)
Czech fiction in the twentieth century has been deeply enmeshed in the nation's political life and often serves as a conduit for its authors' social ideas. Through a series of brilliant and powerful readings of major Czech texts in both literature and history, Peter Steiner challenges the view that literary works can be treated as aesthetically distinct from historical events. Instead, he gives evidence again and again of the inevitable connection between literature and politics.Steiner engages six central works ranging from novels to government documents; all, in his view, purvey ideological fictions that have exerted significant social influence. He begins with Jaroslav Hasek's 1920s novel The Good Soldier Svejk, whose anti-authoritarian protagonist was widely emulated during the Nazi and Communist regimes, and ends with Václav Havel's play The Beggar's Opera, through which Steiner explores the social role of Czech writing in the 1970s. He also considers Reportage, by Julius Fucík, which announces itself as a documentary of the Communist Party's heroic struggle against the Germans, but is, for Steiner, a fiction arising out of Marxist-Leninist ideology; Karel Capek's Apocryphal Stories; Milan Kundera's novel The Joke; and the 1952 show trial of Rudolf Slánský, the general secretary of the Communist Party.